1970
DOI: 10.2307/202411
|View full text |Cite
|
Sign up to set email alerts
|

The Linkage of Historical Records by Man and Computer: Techniques and Problems

Abstract: This article reports the evolution of a method to computerize record linkage in the "Hamilton Project" under the direction of Michael B. Katz at the Ontario Institute for Studies in Education. By record linkage is meant the bringing together of information concerning a particular individual (or even a historical event) from independent sources. In this case there was an attempt to link the names on a census roll of 1851 with those on an assessment roll of 1852 in Hamilton, records which differed in time by onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1976
1976
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Indeed, it was record-linkage projects that, in the 1960s, first pointed to the need to contextualize census data because researchers found that, to an unanticipated extent, different sources did not cumulatively or consistently support the same interpretations of individual or collective lives. The most important scholar working in Canada on the epistemological and philosophical aspects of this topic was Ian Winchester (1970), who collaborated with Michael Katz at the Ontario Institute for Studies in Education.…”
Section: Notesmentioning
confidence: 99%
“…Indeed, it was record-linkage projects that, in the 1960s, first pointed to the need to contextualize census data because researchers found that, to an unanticipated extent, different sources did not cumulatively or consistently support the same interpretations of individual or collective lives. The most important scholar working in Canada on the epistemological and philosophical aspects of this topic was Ian Winchester (1970), who collaborated with Michael Katz at the Ontario Institute for Studies in Education.…”
Section: Notesmentioning
confidence: 99%
“…The extensive literature about this subject, dating back to the early 1970s (Winchester, 1970;Wrigley, 1973), deals with questions as how spelling variants in sources are to be standardised, to what degree linkage can be automated, and what level of relative confidence is acceptable with automated procedures. A final consensus has not yet been reached, in spite of thorough debates, experiments and testing.…”
Section: Other Examplesmentioning
confidence: 99%
“…For a great deal this may be explained by the variety of sources and historical pro blems involved, covering different times and cultures, thus creating an endless range of peculiarities: poll books, census and tax registers, baptism and death records, used for a diversity of research purposes as studying political behaviour, land holding, family reconstruction, life course analysis, regional demo graphy, and prosopography (i.e. using individual data to describe the history of a group 51 ) (Adman, 1997;Adman, Baskerville and Beedham, 1992;Davies, 1992;Harvey and Green, 1994;Harvey, Green and Corfield, 1996;King, 1992King, , 1994Ruusalepp, 2000;Tilley and French, 1997;Vetter, Gonzalez and Gu tmann, 1992;Winchester, 1970).…”
Section: Other Examplesmentioning
confidence: 99%
“…Guth, 1976 andLevenshtein, 1965 algorithms are spelling/string analysis based, whereas Soundex (Winchester, 1970) and Phonex (Lait & Randell, 1998) are phonetic/sound based algorithms. However, most researchers have tried to implement a method which can deal with the culture of names and naming system which are meant to overcome the ethnic problems, e.g.…”
Section: Implementation Of Hybrid Algorithms and System Conceptmentioning
confidence: 99%